BATA BETON CETAK DENGAN BAHAN TAMBAH BILAH BAMBU - R. Agus Murdiyoto; Humran Humran; Wahyunan Arief (Jurnal Poli-Teknologi, 2016)
ABSTRACT The manufacture and test of concrete block has been made with a mixture of cement and sand as 1 : 3 which is also include bamboo as reinforcement with the variation number of 0 (no bamboo), 10; 12 and 14. Parameter of the tests performed include: density test, compressive strength test and water absorption test which is done after the concrete block dried for 28 days. 10 pieces of Concrete block is made for each variation. The results of The density test, it was found that the concrete block of all variations belong to the concrete block for structures with a density around 1809 kg / m³ to 1895 kg / m³. In the compressive strength test, the compressive strength increased in each variation, the highest value goes to the variation 14 with a value of 63 kg / cm². The compressive strength results of the other variations 0; 10 and 12 are 51.55 kg / cm², 50.25 kg / cm² and 55.2 kg / cm². The water absorption test, the value obtained by all the variations ranged from 4.24% to 5.36%, so the sample is include to 1st quality concrete block . Keywords: Bamboo, concrete block, batako, Test. ABSTRAK Telah dilakukan pembuatan dan pengujian bata beton cetak dengan campuran semen dan pasir yaitu 1 : 3 yang didalamnya ditambahankan bilah bambu sebagai tulangan dengan jumlah bervariasi antara 0 (tanpa bilah bambu), 10; 12 dan 14. Parameter pengujian yang dilakukan meliputi : pengujian massa jenis, pengujian kuat tekan dan pengujian daya penyerapan air yang dilakukan setelah bata beton dikeringkan selama 28 hari. Bata beton dibuat sebanyak 10 buah untuk masing-masing variasi. Dari hasil pengujian massa jenis,didapatkan bahwa bata beton dari semua variasi termasuk ke dalam bata beton untuk struktur dengan massa jenis antara 1809 kg/m³ hingga 1895 kg/m³. Pada pengujian kuat tekan, nilai kuat tekan meningkat pada tiap variasinya, hingga nilai paling tinggi terdapat pada variasi 14 dengan nilai 63 kg/cm². Nilai kuat tekan lainnya pada variasi 0; 10 dan 12 adalah masing masing 51,55 kg/cm² , 50,25 kg/cm² dan 55,2 kg/cm². Untuk pengujian daya serap air, nilai yang didapat oleh semua variasi berkisar antara 4,24 % hingga 5,36 % , sehingga termasuk dalam bata beton mutu I. Kata kunci : Bambu, Bata beton, Batako, Pengujian.